Oxidative Coupling of Organoboron Compounds. Issue 6 (12th March 2014) - Dhital, Raghu Nath; Sakurai, Hidehiro
Abstract An increasing number of boron‐mediated reactions have become leading synthetic tools in organic chemistry. The transition‐metal‐catalyzed oxidative coupling reactions of aryl‐ and alkylboron compounds have been intensively studied over recent decades. Palladium‐based catalysts are often used in the presence of an appropriate oxidant, and the reaction mechanism has been fully elucidated. Efficient homocoupling reactions that are catalyzed by nanosized (<2 nm) gold particles were introduced in 2004, which allow the use of oxygen as a sustainable oxidant. Besides palladium and gold, other transition metals and bimetallic combinations can also serve as excellent catalysts. This review summarizes both the seminal early work and recent developments in the area of transition‐metal‐catalyzed oxidative homocoupling reactions of organoboron compounds and discusses the mechanistic details.